In silico identification and in vitro evaluation of MRPS30‐DT lncRNA and MRPS30 gene expression in breast cancer - Nooshafarin Shirani; Roohallah Mahdi‐Esferizi; Reza Eshraghi Samani; Shahram Tahmasebian; Hajar Yaghoobi (Cancer Reports, 2024)
Abstract Background It has been reported that long non‐coding RNAs (lncRNAs) can play important roles in a variety of biological processes and cancer regulatory networks, including breast cancer. Aims This study aimed to identify a novel upregulated lncRNA in breast cancer and its associated gene using bioinformatics analysis, and then evaluate their potential roles in breast cancer. Methods and Results Extensive in silico studies were performed using various bioinformatics databases and tools to identify a potential upregulated breast cancer‐associated lncRNA and its co‐expressed gene, and to predict their potential roles, functions, and interactions. The expression level of MRPS30‐DT lncRNA and MRPS30 was assessed in both BC tissues and cell lines using qRT‐PCR technology. MRPS30‐DT lncRNA and MRPS30 were selected as target genes using bioinformatics analysis. We found that MRPS30‐DT and MRPS30 were significantly overexpressed in BC tissues compared with normal tissues. Also, MRPS30 showed upregulation in all three BC cell lines compared with HDF. On the other hand, MRPS30‐DT significantly increased in MDA‐MB‐231 compared with HDF. While the expression of MRPS30‐DT was significantly dropped in the resistance cell line MCF/MX compared to HDF and MCF7. Moreover, bioinformatics analysis suggested that MRPS30‐DT and MRPS30 may play a potential role in BC through their involvement in some cancer signaling pathways and processes, as well as through their interaction with TFs, genes, miRNAs, and proteins related to carcinogenesis. Conclusions Overall, our findings showed the dysregulation of MRPS30‐DT lncRNA and MRPS30 may provide clues for exploring new therapeutic targets or molecular biomarkers in BC.